Reduced structural connectivity in non-motor networks in children born preterm and the influence of early postnatal human cytomegalovirus infection - Pretzel, Pablo; Wilke, Marko; Tournier, J-Donald; Goelz, Rangmar; Lidzba, Karen; Hauser, Till-Karsten; Groeschel, Samuel (Frontiers in Neurology, 2023)
Introduction Preterm birth is increasingly recognized to cause lifelong functional deficits, which often show no correlate in conventional MRI. In addition, early postnatal infection with human cytomegalovirus (hCMV) is being discussed as a possible cause for further impairments. In the present work, we used fixel-based analysis of diffusion-weighted MRI to assess long-term white matter alterations associated with preterm birth and/or early postnatal hCMV infection. Materials and methods 36 former preterms (PT, median age 14.8 years, median gestational age 28 weeks) and 18 healthy term-born controls (HC, median age 11.1 years) underwent high angular resolution DWI scans (1.5 T, b = 2 000 s/mm2, 60 directions) as well as clinical assessment. All subjects showed normal conventional MRI and normal motor function. Early postnatal hCMV infection status (CMV+ and CMV−) had been determined from repeated screening, ruling out congenital infections. Whole-brain analysis was performed, yielding fixel-wise metrics for fiber density (FD), fiber cross-section (FC), and fiber density and cross-section (FDC). Group differences were identified in a whole-brain analysis, followed by an analysis of tract-averaged metrics within a priori selected tracts associated with cognitive function. Both analyses were repeated while differentiating for postnatal hCMV infection status. Results PT showed significant reductions of fixel metrics bilaterally in the cingulum, the genu corporis callosum and forceps minor, the capsula externa, and cerebellar and pontine structures. After including intracranial volume as a covariate, reductions remained significant in the cingulum. The tract-specific investigation revealed further reductions bilaterally in the superior longitudinal fasciculus and the uncinate fasciculus. When differentiating for hCMV infection status, no significant differences were found between CMV+ and CMV−. However, comparing CMV+ against HC, fixel metric reductions were of higher magnitude and of larger spatial extent than in CMV− against HC. Conclusion Preterm birth can lead to long-lasting alterations of WM micro- and macrostructure, not visible on conventional MRI. Alterations are located predominantly in WM structures associated with cognitive function, likely underlying the cognitive deficits observed in our cohort. These observed structural alterations were more pronounced in preterms who suffered from early postnatal hCMV infection, in line with previous studies suggesting an additive effect.